BS EN ISO 15493 AMD11. Plastics piping systems for industrial applications. Acrylonitrile-butadiene-styrene (ABS), unplasticized poly(vinyl chloride) (PVC-U) and chlorinated poly(vinyl chloride) (PVC-C). Specifications for components and the system. Metric series. (1st July 2021) - British Standards Institution,
No abstract available